2016
DOI: 10.3389/fpsyg.2016.01777
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Writing of Deaf or Hard-of-Hearing Students and Normal-Hearing Peers from Complex Network Approach

Abstract: Deaf or hard-of-hearing individuals usually face a greater challenge to learn to write than their normal-hearing counterparts. Due to the limitations of traditional research methods focusing on microscopic linguistic features, a holistic characterization of the writing linguistic features of these language users is lacking. This study attempts to fill this gap by adopting the methodology of linguistic complex networks. Two syntactic dependency networks are built in order to compare the macroscopic linguistic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 71 publications
(129 reference statements)
1
7
0
Order By: Relevance
“…During the senior high school years, to has the highest degrees, becoming the most important vertex in networks. These findings are consistent with previous findings that function words such as articles and prepositions tend to be hubs of a network (Ferrer-i-Cancho and Solé, 2001; Cong and Liu, 2014; Jin and Liu, 2016). These hubs, i.e., the copula be and other function words, exists even in network P 4 , which may account for the absence of the phase shift, that is, the sudden emergence of scale-free property in L2 learning.…”
Section: Discussionsupporting
confidence: 93%
“…During the senior high school years, to has the highest degrees, becoming the most important vertex in networks. These findings are consistent with previous findings that function words such as articles and prepositions tend to be hubs of a network (Ferrer-i-Cancho and Solé, 2001; Cong and Liu, 2014; Jin and Liu, 2016). These hubs, i.e., the copula be and other function words, exists even in network P 4 , which may account for the absence of the phase shift, that is, the sudden emergence of scale-free property in L2 learning.…”
Section: Discussionsupporting
confidence: 93%
“…The centrality of a node reflects its importance and authority in the complex network. It is usually defined by different measures, such as degree centrality, betweenness centrality and closeness centrality (Jin and Liu, 2016). Degree centrality quantifies the number of edges which are directly linked to the vertices.…”
Section: Network Parametersmentioning
confidence: 99%
“…Prior studies demonstrate the feasibility of using the complex network approach to characterize and classify human languages, including the exploration of statistical patterns of different languages, stylistic research (Ferrer-i-Cancho et al, 2004;Liu, 2008a), typological properties of languages (Liu and Xu, 2011), hierarchical structures of a language (Chen et al, 2015), the evolution of languages (Cui et al, 2017;Chen et al, 2018), and linguistic features in language learning (Jin and Liu, 2016;Jiang et al, 2019;Hao et al, 2021). It is probable that network properties can also discriminate linguistic features of different interpreting types.…”
Section: Introductionmentioning
confidence: 99%
“…The implicit meaning of the deep structure may be extracted by analysis of the surface structure (Bransford and Johnson, 1972;Fodor, 1974). Jin and Liu (2016) used modern Chinese as an example to study the structural features of human language as a multi-level system using a complex network method. Jin and Liu found that the four network models of Chinese (which are character co-occurrence, word co-occurrence, syntactic relationship, and semantic relationship) present their respective statistical characteristics and reflect the commonalities and connections on all levels of the system.…”
Section: The Use Of Graphs In the Evaluation Of Writingmentioning
confidence: 99%